Development of Pop-Up Book Learning Media in Mathematics Subject on Plane Figures Material for Grade III at SD Negeri 064965 Medan. - Sinulingga, Anzelina Br; Pulungan, Lilik Hidayat (AlAdzkiya International of Education and Sosial (AIoES) Journal, 2026)
This study aims to: (1) determine how the Pop-Up Book learning media product is developed for the topic of plane figures, (2) determine the validity level of the media, and (3) determine the practicality level of the media. The method used in this study was the Research and Development (R&D) method. The development model applied in this research was the 4D development model consisting of four stages: (1) define, (2) design, (3) development, and (4) dissemination, introduced by Sivasailam Thiagarajan. This research produced a Pop-Up Book multiplication learning media for elementary schools. Based on the validation results of the learning media, the average scores were 91% from material experts, 93% from media experts, and 96% from language experts, indicating that the learning media met the “very feasible” criteria. The practicality results showed that the teacher response reached 92% and the student response reached 95%, indicating that the learning media met the “very practical” criteria. Based on these findings, it can be concluded that the Pop-Up Book learning media was declared highly feasible/valid and highly practical.